2010
DOI: 10.1186/1471-2334-10-211
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir for treatment and prevention of pandemic influenza A/H1N1 virus infection in households, Milwaukee, 2009

Abstract: BackgroundDuring an influenza pandemic, a substantial proportion of transmission is thought to occur in households. We used data on influenza progression in individuals and their contacts collected by the City of Milwaukee Health Department (MHD) to study the transmission of pandemic influenza A/H1N1 virus in 362 households in Milwaukee, WI, and the effects of oseltamivir treatment and chemoprophylaxis.Methods135 households had chronological information on symptoms and oseltamivir usage for all household membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 20 publications
1
57
0
3
Order By: Relevance
“…Three studies reported that both SIR PCR and SIR FARI were higher among household contacts of younger index cases, 22,25,33 two studies reported that they were lower with younger index cases, 19,29 and one study found no difference by index age. 41 Four studies that stratified by sex found no difference in SIRs, 27,34,40,41 while one study reported female contacts to be at greater risk of infection 24 and another that adult women were more likely to transmit pH1N1 to children.…”
Section: Resultsmentioning
confidence: 96%
“…Three studies reported that both SIR PCR and SIR FARI were higher among household contacts of younger index cases, 22,25,33 two studies reported that they were lower with younger index cases, 19,29 and one study found no difference by index age. 41 Four studies that stratified by sex found no difference in SIRs, 27,34,40,41 while one study reported female contacts to be at greater risk of infection 24 and another that adult women were more likely to transmit pH1N1 to children.…”
Section: Resultsmentioning
confidence: 96%
“…Family size and the number of children are recognized as risk factors for household transmission in previous studies [5], [28], [29]. However, contact between patients and healthy persons in the household could differ based on cultural and familial factors and the size of the house [24].…”
Section: Discussionmentioning
confidence: 99%
“…11 Thirdly, the present study was underpowered to determine significant reductions in the risk of household transmission during antiviral prophylaxis, therefore the findings on the Oseltamivir treatment within 24 h was, however, shown to yield an odds ratio of 0.62, which was not statistically significant, but is broadly consistent with published studies. 13,15 The simple adjustment of the age-effect in the statistical model may not have been enough to correct for confounding factors. This is also a problem when an age-specific treatment strategy is employed.…”
Section: Discussionmentioning
confidence: 99%